Gas-phase study on the C-C coupling of naphthol catalyzed by Cu IITMEDA: evidence for the key role of binuclear clusters - Roithová, Jana; Schröder, Detlef (Chemistry, 2008)
The mechanism of oxidative coupling of two naphthol molecules to form binaphthol catalyzed by Cu(OH)ClTMEDA (TMEDA=N,N,N',N'-tetramethylethylenediamine) was approached by means of a gas-phase model system. Concise evidence is provided that the coupling reaction proceeds in clusters with two Cu(II) centers, whereby the intermediacy of free naphthoxy radicals in the coupling step is avoided. In the absence of TMEDA, the cluster is bound via a bridging counterion and the coupling reaction is followed by cluster cleavage. The coordination of one or two TMEDA molecules to the reactive complex results in more efficient coupling of naphthol molecules, and moreover, the binuclear cluster is also conserved after the reaction is completed. The effect of TMEDA is twofold: First, it supports clustering of copper and, second, as a ligand bound to a copper center in the reactive complex, it weakens the bond between copper and the naphtholato ligand such that the naphtholato unit is more prone to undergo C--C coupling. Furthermore, a pronounced counterion effect is found that correlates well with condensed-phase data: weakly bridging counterions (e.g., NO3(-)) yield less stable dicopper clusters and the coupling reaction hardly occurs, whereas better bridging counterions (e.g., Cl(-) or Br(-)) provide more stable clusters that make the coupling reaction more efficient.
Keywords: Ethylenediamines; Molecular Structure; Naphthols; uhlík; Catalysis; Financing, Organized; organokovové sloučeniny; financování organizované; Gases; katalýza; ethylendiaminy; Ligands; měď; naftoly; ligandy; Copper; Organometallic Compounds; Carbon; plyny; molekulární struktura